Odpowiedzi

2010-01-08T15:03:15+01:00
A)x²-2x+x-2+x²-x+2x-2=x²-4=(x+2)(x-2)
b)(5k+n)(k-2n)-k(4k+n)=5k²-10kn+kn-2n²-4k²-kn=k²-9kn-2n²
c)(4y+3)(y-2)-2y(4-2)=4y²-8y+3y-6-8y+4=4y²-13y-2
d))(3c-2)(c-1)-c(c-2)=3c²-3c-2c+2-c²+2c=2c²-3c+2
e)2(3a²-1)-(a+2)(a+2)=6a²-2-a²-2a-2a-4=5a²-4a-6
f)5x²(x2+1)-(x²-2)(x²+3)=10x do czwartej+5x²-x do czwartej-3x²+2x²+6=9x do czwartej+4x²+6
Najlepsza Odpowiedź!
2010-01-08T16:23:38+01:00
A)(x+1)(x-2)+(x+2)(x-1)=x²-2x+x-2+x²-x+2x-2=2x²-4
b).(5k+n)(k-2n)-k(4k+n) =5k²-10kn+kn-2n²-4k²-kn=k²-20kn-2n²
c)(4y+3)(y-2)-2y(4-2y) = 4y²-8y+3y-6-8y+4y²=8y²-13y-6
d))(3c-2)(c-1)-c(c-2)=3c²-3c-2c+2-c²+2c=2c²-3c+2
e)2(3a²-1)-(a+2)(a+2)=6a²-2-a²-2a-2a-4=5a²-4a-6
f)5x²(x2+1)-(x²-2)(x²+3)=10x do czwartej+5x²-x do czwartej-3x²+2x²+6=9x do czwartej+4x²+6